Emotions of food influencers regarding digital work and the transmission of food knowledge on Instagram - Mairano Maria Victoria (Online Media and Global Communication)
This article aims to problematize influencers’ emotional ecologies regarding their digital work as content generators and the emotional ecologies recorded in the food practices they share on their profiles.